2018
DOI: 10.5114/jcb.2018.79713
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal toxicity after high-dose-rate endovaginal brachytherapy: 20 years of results

Abstract: PurposeTo evaluate vaginal toxicity (primary endpoint) and local control (secondary endpoint) in patients with endometrial cancer who underwent primary surgery and adjuvant high-dose-rate (HDR) endovaginal brachytherapy (BT).Material and methodsIn September 2017, the authors conducted a comprehensive literature search of the following electronic databases: PubMed, Web of Science, Scopus, and Cochrane library. In this systematic review, the authors included randomized trials, non-randomized trials, prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 61 publications
(184 reference statements)
3
24
0
1
Order By: Relevance
“…Regarding late toxicity, our review showed that the treatment is very well tolerated. The main side effects consisted of grade G1-G2, while G3-G4 late vaginal toxicities have been reported only in few cases (range, 0-8%) in line with the current data in literature [49,50].…”
Section: Discussionsupporting
confidence: 88%
“…Regarding late toxicity, our review showed that the treatment is very well tolerated. The main side effects consisted of grade G1-G2, while G3-G4 late vaginal toxicities have been reported only in few cases (range, 0-8%) in line with the current data in literature [49,50].…”
Section: Discussionsupporting
confidence: 88%
“…The development of short-term side effects was based on two large trials. [28,29] The probability of bilateral SLN mapping is 79%. [19] The sensitivity of 97% for SLN mapping is based on a study by Rossi et al [14] The specificity is assumed to be 100%, since no false positive outcomes are possible with SLN.…”
Section: Probabilities Decision Treementioning
confidence: 99%
“…The role of exclusive VBT as a standard treatment in high-intermediate-risk EC patients has been recently confirmed by the long-term results of PORTEC-2 trial, in which, a dose of 21 Gy in 3 fractions of 7 Gy was delivered with one week interval between each fraction, and with the dose specified at 5 mm distance from the surface of cylinder [7]. Quite different fractionations and dose intensity (overall treatment time) schedule has been reported in literature, with local control ranging from 90% to 100% and with a rate of late vaginal toxicity, mainly G1-G2, ranging from 7.5% to 27.7% [6]. Other VBT schedules, which are used frequently include 5 Gy at 5 mm in 6 fractions, 5 Gy at 5 mm in 5 fractions, 7 Gy in 3 fractions at mucosa surface, and 5 Gy at 5 mm in 4 fractions [13].…”
Section: Discussionmentioning
confidence: 99%
“…A firm conclusion has been drawn from a randomized PORTEC-2 trial, which reported similar rates of locoregional relapse in early-stage EC patients with intermediate-risk who receive exclusive VBT, when compared with pelvic EBRT [3]. Although VBT as monotherapy represents now the standard adjuvant treatment for early-stage EC, including intermediate-(IR) and high-intermediate-risk (HIR) disease, there is a large variability among fractionations or total dose or dose intensity delivery [2,4,5,6,7,8]. Despite this high variability of fractionations, VBT has been related to satisfied rate of local control, ranging from 90% to 100%, and low-rate of late vaginal toxicity, mainly G1-G2, with a range from 7.5% to 27.7% [6].…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation